2013
DOI: 10.5901/ajis.2013.v2n3p123
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Parenting Styles on the Social Development of Children

Abstract: The purpose of the study was to ascertain the dominant parenting styles of parents in the study area

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 13 publications
5
29
0
6
Order By: Relevance
“…The results of this study are in line with the results of research by Mensah and Kuranchie [9] which states that the parenting style that gives a significant influence on social competence is the Authoritative parenting and Authoritarian parenting. Children who have authoritative parents are found to have good social competence while children with authoritarian parents are found to have poor social competence.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The results of this study are in line with the results of research by Mensah and Kuranchie [9] which states that the parenting style that gives a significant influence on social competence is the Authoritative parenting and Authoritarian parenting. Children who have authoritative parents are found to have good social competence while children with authoritarian parents are found to have poor social competence.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, it is found that only authoritative parenting and authoritarian parenting are sign5ificant predictors to social competence that contribute to 20.8% and 19.7% respectively. The findings of this study is supporting prior research which state that parenting style play significant role in developing children social competence [9][10] [11].…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, in his pioneering research Baum rind identified three parenting styles as follows (Mensah & Kuranchie, 2013):…”
Section: Literature Reviewmentioning
confidence: 99%
“…6 Hasil penelitian menunjukkan bahwa terdapat hubungan antara pola asuh orang tua dengan kemampuan sosialisasi anak. Penelitian ini sesuai dengan beberapa penelitian yang melaporkan bahwa pola asuh berhubungan dengan kemampuan sosialisasi anak [17][18][19][20][21][22][23] Interaksi antara orang tua dan anak merupakan dimensi penting dalam pola asuh, terdapat kehangatan dan strategi kontrol. Hubungan orang tua dan anak yang optimal erat kaitannya dengan kemampuan sosialisasi anak dan hubungan dengan teman sebaya.…”
Section: Hasilunclassified